Changes in apoptosis and Bcl-2 expression in human hyperglycemic, term placental trophoblast - Sgarbosa, Fabio [UNESP]; Barbisan, Luis Fernando [UNESP]; Brasil, Maria A. M. [UNESP]; Costa, Elaine [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Goncalves, Claudia R.; Bevilacqua, Estela [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Elsevier B.V., 2006)
Apoptosis and its associated regulatory mechanisms are physiological events crucial to the maintenance of placental homeostasis; imbalance of these processes, however, such as occurs under various pathological conditions, may compromise placenta function and, consequently, pregnancy success. Increased apoptosis occurs in the placentas of pregnant women with several developmental disabilities, while increased Bcl-2 expression is generally associated with pregnancy-associated tumors. Herein, we tested the hypothesis that apoptosis-associated disturbs might be involved in the placental physiopathology subjected to different maternal hyperglycemic conditions.Thus, in the present study we investigated and compared the incidence of apoptosis using TUNEL reaction and Bcl-2 expression, in term-placentas of normoglycemic, diabetic and daily hyperglycemic patients. Tissue samples were collected from 37 placentas, being 15 from healthy mothers with normally delivered healthy babies, and 22 from mothers with glucose disturbances. From these latter 22 patients, 10 showed maternal daily hyperglycemia and 12 were clinically diabetics. Both Bcl-2 expression and apoptotic DNA fragmentation were established and quantified in the trophoblasts of healthy mothers. Compared to these reference values, a higher apoptosis index and lower Bcl-2 expression were disclosed in the placentas of the diabetic women, while in the daily hyperglycemic group, values were intermediate between the diabetic and normoglycemic patients. The TUNEL/Bcl-2 index ratio in the placentas varied from 0.02 to 0.09 for pregnant normoglycemic and diabetic women, respectively, revealing a predominance of apoptosis in the diabetic group. Our findings suggest that hyperglycemia may be a key factor evoking apoptosis in the placental trophoblast, and therefore, is relevant to diabetic placenta function. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: diabetes; cell death; proliferation; syncytiotrophoblast; TUNEL reaction